Student exchange programme between the International Islamic University Malaysia and the Universitas Muhammadiyyah Yogyakarta: An overview - Wan Muhammad, Ramizah; Shuaib, Farid Sufian (2013)
Student exchange programmes in the content of relationships between universities and academic structures are useful in improving the quality of higher education. This program has benefited the students as well as the universities. This paper is to highlight the experience of these two universities through the report that we received in 2011 and 2012. This paper will examine the programmes that we had so far that can be improved and modified to suit with the necessary7 circumstances. At the same time, this paper will highlight the feedback from the students who have participated in this programmes that they benefitted a lot and things